Penyegaran Screening Penyakit Tidak Menular serta Konsumsi Bahan Herbal pada Masyarakat - Novita Dewi; Supriyadi Supriyadi; Ika Cahyaningrum (Jurnal Abdimas Kesehatan (JAK), 2022)
The main problem in the health sector lately is Non-Communicable Diseases (NCD). NCD causes death due to complications they experience. NCD in the form of hypertension, hyperuresemia and Diabetes Mellitus Type 2 (DMT2), and others. Consumption of herbal ingredients contributes non-pharmacologically to the occurrence of non-communicable diseases. Initial screening of this non-communicable disease and consumption of herbal ingredients is one of the prevention of further complications from this non-communicable disease. The purpose of community service in the form of refreshing non-communicable disease screens is very useful for the community in the context of preventive and promative NCD. This refreshment was carried out in conjunction with community activities who underwent healthy walks in order to enliven the 77th Indonesian Independence Day, there were 57 contestants registered for health checks. The method, which is carried out with a problem approach to the community, is carried out from 07.30 to 10.30 WIB. The results of the abdimas found that there were 16.2% of the population experienced hypertension, 42% had hyperuresemia and 19% experienced hyperglycemia, and 2.9% of the population consumed herbal ingredients. The next abdimas recommendation is to educate PTM and herbal ingredients based on local wisdom.